Królestwo Jordanii w polityce Stanów Zjednoczonych wobec Bliskiego Wschodu w okresie pozimnowojennym - Czornik, Katarzyna (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: The Kingdom of Jordan in the US foreign policy towards the Middle East in the post‑Cold War era The US — Jordan relations, both during and after the Cold War, can be described as close, based on the pursuit of common goals and mutual respect. Although the United States of America and the Kingdom of Jordan have never concluded a formal treaty with each other, they cooperated on many levels, in the Middle‑Eastern region and internationally, both during the second half of the 20th century and in the first two decades of the 21st century. Despite the complex geopolitical situation in the Middle East, re‑occurring threats and challenges that may have weakened the bilateral relations between the two states, the informal alliance between the US and Jordan have survived, which is indicative of the importance of these relations and the strength of the partnership. The place and role of Amman in the foreign policy of Washington have many aspects and dimensions. One can observe certain evolution of the position that consecutive American governments attributed to Jordan depending on conditions that have been both extra‑regional (the Cold War rivalry between the US and the Soviet Union) and intra‑regional (the three Gulf Wars, the Middle‑Eastern peace process). It is also important to emphasize that after the collapse of the Eastern Bloc, the mutual relations have gained a different, more strategic dimension. Hence, it can be argued that Jordan’s importance in the US foreign policy has only reached its pinnacle during the post‑Cold War era. The present article seeks to pinpoint the place and role of the Kingdom of Jordan in the US policy towards the Middle East after the Cold War and to define the character of the relationship between the two states. Its main goal is to identify and describe both positive and negative factors determining the US — Jordan relations. The article will also attempt to answer the questions about the extent to which the Arab Spring has influenced the shape of the mutual links between Washington and Amman. Key words: United States of America, Middle East, Jordan, foreign policy